Visualizing stellate ganglion with US imaging for guided SGB treatment: A feasibility study with healthy adults - Li, Jia; Pu, Shaofeng; Liu, Zihao; Jiang, Lixin; Zheng, Yuanyi (Frontiers in Neuroscience, 2022)
Objective: As for ultrasound (US) guide stellate ganglion (SG) block, unsatisfactory curative outcomes and complications still remain. This problem could be greatly improved by identifying and monitoring SG. To our knowledge, almost no studies have been conducted to directly visualize SG. This study explored the feasibility of detection of SG and to summarize the findings of SG through US. Methods: 50 health adults with 100 SGs were enrolled. The size, shape, echogenicity, margin, the inferior pole of SG, the relationship between the superior pole of SG and the transverse process, and the relationship of the superior pole of SG to the inferior thyroid, and the relationships between SG and other surrounding tissues were evaluated on US. Results: The SG was identified in 79%. No significant differences were found between the right and left regarding thickness, CSA and position (all p＞0.05), however, there was significant difference in width of the right and left (p＜0.05). The side was associated with SG visibility (p＜0.05), however, the gender were not (p＞0.05). 42% SGs were oval-shaped. All SGs were hyperechogenicity and ill-defined margin. 63% SGs lied C7 transverse process level. 77% SGs were located under the inferior thyroid artery. All SGs lied lateral to the thyroid, medial to the anterior scalene muscle and vagus nerve. Conclusions: Our preliminary study demonstrates that US imaging provides the capability of detecting SG. This may be helpful in minimizing complications and improving the accuracy of US-guided SG block.